In vitro evaluation of acidified toothpastes with low fluoride content - Brighenti, Fernanda Lourenção [UNESP]; Delbem, ACB; Buzalaf, MAR; Oliveira, FAL; Ribeiro, D. B.; Sassaki, K. T. (Karger, 2006)
Fluoride toothpastes are a risk factor for the development of dental fluorosis. Products with low fluoride content offer a higher security, but their effectiveness must be proven. The aim of this in vitro study was to compare two acidified toothpastes with low fluoride concentration (412 and 550 mu g F/g) with neutral toothpastes. Bovine enamel blocks were selected by surface microhardness (SMH) and randomized to twelve groups of 13, according to the fluoride concentration in toothpaste (placebo, 275, 412, 550 or 1,100 jig F/g) and pH (7.0 or 5.5). Two commercially available toothpastes were also studied: a 1,100-mu g F/g, pH 7.0 paste (positive control) and a children's paste (500 mu g F/g, pH 7.0). The blocks were subjected to pH cycling for 7 days. The toothpaste treatment was done twice daily. Surface and cross-sectional microhardnesses were assessed to calculate the percentage change of SMH (%SMH) and the mineral loss (Delta Z). The amount of fluoride, calcium and phosphorus in the solutions after the pH cycling was also analyzed. Compared to neutral toothpastes, the acidified toothpastes reduced the %SMH in all F concentrations. Higher F and lower Ca and P concentrations were found in solutions for the acidified toothpastes. Regarding AZ, only the positive control, 1,100-mu g F/g (acidified and neutral) groups were not statistically different. The acidified toothpastes showed a dose-response relationship with all variables. For the low-fluoride toothpastes evaluated, only the 550-mu g F/g acidified paste had the same anticariogenic action as the 1,100-mu g F/g neutral paste.
Keywords: demineralization; dental caries, prevention and control; dental enamel; fluoride; toothpaste